Digitalizing Zakat: Enhancing Muzakki Loyalty through E-Service Quality and Institutional Image in Indonesia - Alfia Bella Winanda (Zamzami Scholar Publishing, 2026)
The digital transformation of Islamic philanthropy has reshaped donor behavior, yet the mechanism binding technology and long-term loyalty remains underexplored. This study examines the impact of digital zakat service quality on muzakki loyalty, while incorporating institutional image as a moderating variable. Employing a quantitative approach with an associative causal design, the research surveyed 72 active digital donors of Lazismu East Java using purposive sampling. Data were analyzed using Moderated Regression Analysis (MRA) via IBM SPSS 20. The findings reveal that digital service quality has a significant influence on loyalty (t = 6.769, B = 0.629), confirming that efficiency and transparency are primary drivers of retention. Crucially, institutional image functions as a quasi-moderator (Sig. = 0.028), effectively strengthening the causality between technical service performance and donor commitment. These results suggest that while technology serves as an engine for efficiency, institutional reputation acts as a trust anchor. The study contributes to the literature by demonstrating that hybrid strategies combining high-tech service and high-trust branding are essential for sustaining muzakki loyalty in the competitive digital era.